Strengthening The Coordination Function of The Forestry Ministry: Legal Reform in The “Merah Putih” Cabinet For Modern Bereaucracy - Rahmi, Elita; Fitria, Fitria; Nuriyatman, Eko; Yuwono, Teguh; Toscany, Afrizal Nehemia (Faculty of Law, Universitas Negeri Semarang, 2025)
This study aims to evaluate how the coordination function of the Ministry of Forestry has been strengthened following its separation from the Ministry of Environment. This separation seeks to ensure that the Ministry of Forestry does not cultivate sectoral egos that hinder forest conservation efforts in Indonesia, thereby promoting a modern bureaucracy, mutual oversight, and balanced management of forestry as a crucial and strategic government priority, especially in light of the ongoing transition of forests to non-forestry uses since the reform era. Weak coordination can significantly affect forest protection, which is inherently tied to legal and justice issues. The “Merah Putih” Cabinet is the most significant cabinet since the New Order Era through the reform era, likely resulting in numerous vertical and horizontal coordination challenges that could obstruct the effective management of various tasks, functions, and ministerial roles. This research employs a normative juridical method with legislative, conceptual, and historical perspectives. In conclusion, there is a need to evaluate internal and external strengthening among ministries. The structure of an independent forestry ministry is not adequately aligned with its responsibilities and functions in managing Indonesia’s forest resources and potential natural wealth as a prosperous nation. It is vital to assess the role of the coordinating minister overseeing the Ministry of Forestry, as placing forestry issues under the Coordinating Ministers for Food, Maritime Affairs, and Economic Affairs does not sufficiently address forestry challenges, which are more related to the laws governing the conservation of living organisms and their intact, integrated ecosystems.